Postoperative follow-up for gastric cancer needs to be individualized according to age, tumour recurrence pattern, and recurrence time. Issue 8 (August 2022) - Qiu, Wen-Wu; Chen, Qi-Yue; Zheng, Wen-Ze; He, Qi-Chen; Huang, Ze-Ning; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; et al.
Abstract: Background: Few studies have reported the association between the pattern and time point of recurrence in different groups stratified by age in postoperative survival of patients with gastric cancer. Methods: The clinicopathological data and recurrence data of 2028 patients with GC who underwent curative surgery from January 2010 to March 2015 were enrolled in this study. Patients were grouped according to age: young group (YG) (≤45 years old) (n = 180) and non-young group (OG) (>45 years old) (n = 1848). Results: A total of 2028 patients were enrolled. The young group had better 5-year OS and DFS than the non-young group. In peritoneal recurrence, the cumulative incidence of recurrence in YG was higher than that in OG (P < 0.001). In distant recurrence, the cumulative incidence of recurrence YG was always lower than that of OG (P = 0.004). Recurrence hazard function varied over time between the two groups:in the peritoneal metastasis, the recurrence hazard for YG was higher and earlier than that of OG and the YG was observed during five years after surgery with two recurrence peaks in 8.5 months and in 41.5 months. In distant recurrence, the recurrence hazard for OG had an earlier and higher single peak than that of YG (6.0 months). Conclusion: The recurrence characteristics of patients with gastric cancer after curative resection between young group and older group are different. Personalized follow-up strategies should be developed according to the age and time point after operation for the early detection of recurrence and making decision for further treatment.